Studi Faktor Pendukung Popularitas Multiplayer Online Battle Arena dengan Pendekatan Kuantitatif - Tony Wibowo (ULTIMA InfoSys, 2021)
One of the most popular video game genre nowadays is Multiplayer Online Battle Arena (MOBA). This genre has become the one genre to go in a multiplayer and competitive setting. This study aims to answer what makes this genre become so popular compared to another genre. The quantitative approach was used to gather a consensus of respondents that will give insight to the population's condition. By using Both DeLone & McLean and UTAUT2 model, it was found that the factors that influence MOBA popularity are Information Quality, Service Quality, Habit, Hedonic Motivation and Social Motivation. These findings show that MOBA usage are still very much influenced by social factor rather than mechanic aspect of video game. Index Terms—MOBA; DeLone & McLean; UTAUT2